The effect of Trendelenburg positioning in laparoscopic colorectal surgery on intraocular pressure and cognitive function - Vitish-Sharma, Parveen (2018)
Trendelenburg positioning is frequently used during laparoscopic surgery particularly when access to the pelvis is required. With improvements in laparoscopic skills, high risk patients and more complex procedures are now frequently being performed laparoscopically. (Improvement, 2016) The aim of this thesis is to investigate the effect of Trendelenburg positioning on intraocular pressure (IOP) and cognitive function.